Reimagined history and local patriotism: rural youth activism in Cigombong, Indonesia - Gandi, Rajib; Kolopaking, Lala M.; Damanhuri, Didin S.; Sjaf, Sofyan (Frontiers in Political Science, 2025)
Rural youth movements in Indonesia have long been marginalized within national narratives, despite their deep historical roots in local struggles that shaped collective consciousness and community resilience. This study reinterprets the history of rural youth activism in Cigombong, Bogor Regency, Indonesia, as a form of resistance rooted in collective memory, community values, and symbolic practices in response to the expansion of corporate capitalism in rural areas. Utilizing an ethnographic and historical-tracing approach combined with quantitative data from 151 rural youth activists, the research explores the transformation of youth agency from the colonial era to the digital age and examines how local history is reactivated as both a symbolic and political resource. The findings reveal that local patriotism, manifested through collective action, cultural expression, and net-activism, has generated new forms of community-based resistance. By integrating the theory of social fields and the framework of collective memory, this article underscores the importance of reinterpreting local history as a strategy to strengthen the resilience and autonomy of rural youth in shaping their own futures, contributing to sociological discourse on rural youth activism, lived space, and grassroots nationalism in the platform era.